2017
DOI: 10.1111/add.14059
|View full text |Cite
|
Sign up to set email alerts
|

Associations between methadone maintenance treatment and crime: a 17‐year longitudinal cohort study of Canadian provincial offenders

Abstract: Among a cohort of Canadian offenders, rates of violent and non-violent offending were lower during periods when individuals were dispensed methadone compared with periods in which they were not dispensed methadone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 53 publications
1
41
0
3
Order By: Relevance
“…Whereas some research assumes a correlation between impaired impulse control and criminal behavior [19, 73-75], we did not find any relation between BIS-11 scores and the number of convictions or months of imprisonment. Other studies suggest a decrease in crime rates as a result of the methadone maintenance program itself [76]. Hepatitis as result of needle-sharing can be considered another “real-life” indicator for impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some research assumes a correlation between impaired impulse control and criminal behavior [19, 73-75], we did not find any relation between BIS-11 scores and the number of convictions or months of imprisonment. Other studies suggest a decrease in crime rates as a result of the methadone maintenance program itself [76]. Hepatitis as result of needle-sharing can be considered another “real-life” indicator for impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have consistently reported OST to be associated with suppression of illicit opioid use (e.g. Hubbard et al, 2003;Mattick et al, 2014Mattick et al, , 2009Simpson et al, 1982;Teesson et al, 2006), a lower risk of opioid overdose (White et al, 2015), and reductions in crime (Russolillo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, OMTs improve the overall functioning of opioid dependence patients [22,24,25], and have thus allowed improving the recovery trajectory of many opioid users. At a societal level, methadone and buprenorphine have even been shown to lower the rate of crimes committed by subjects with opioid dependence [26]. Methadone and buprenorphine have also demonstrated a good cost-effectiveness ratio in the context of developed countries [27,28].…”
Section: Current Best Treatments For Opioid Dependencementioning
confidence: 99%